High-dose hypofractionated radiotherapy is effective and safe for tumors in the head-and-neck. (September 2016) - Teckie, Sewit; Lok, Benjamin H.; Rao, Shyam; Gutiontov, Stanley I.; Yamada, Yoshiya; Berry, Sean L.; Zelefsky, Michael J.; Lee, Nancy Y.
Highlights: Hypofractionated head and neck radiation therapy is controversial due to toxicity concerns. 62 sites of measurable head-and-neck tumors were treated with high-dose radiation therapy. Dose per fraction of 6 Gy or greater had improved locoregional control. Re-irradiated patients had worse disease control after hypofractionated radiation. No increased toxicity was seen in patients treated with higher doses per fraction. Abstract: Objectives: High-dose, hypofractionated radiotherapy (HFRT) is sometimes used to treat malignancy in the head-and-neck (HN), both in the curative and palliative setting. Its safety and efficacy have been reported in small studies and are still controversial. Materials and methods: We retrospectively evaluated the outcomes and toxicities of HFRT, including ultra-high-dose fractionation schemes (⩾8 Gray per fraction), for HN malignancies. Results: A total of 62 sites of measurable gross disease in 48 patients were analyzed. The median follow-up was 54.3 months among five survivors and 6.0 months in the remaining patients. Median RT dose was 30 Gray in 5 fractions; 20/62 lesions (32%) received dose-per-fraction of ⩾8 Gray. Overall response rate at first follow-up was 79%. One-year local-progression free rate was 50%. On multivariate analysis for locoregional control, dose-per-fraction ⩾6 Gray was associated with control ( p = 0.04) and previous radiation was associated with inferior control ( p = 0.04). Patients who achieved complete response to RT had longer survival than those who did not ( p = 0.01). Increased toxicity rates were not observed among patients treated with dose-per-fraction ⩾8 Gray; only re-irradiation increased toxicity rates. Conclusion: Despite the poor prognostic features noted in this cohort of patients with HN malignancies, HFRT was associated with high response rates, good local control, and acceptable toxicity. Sites that were treated with 6 Gray per fraction or higher and had not been previously irradiated had the best disease control. A prospective trial is warranted to further refine the use and indications of HFRT in this setting.